Coronal caries : evolving evidence and clinical practice - Carvalho, Joana Christina (Basel, Switzerland : Karger, 2023)
The disease dental caries and in particular coronal caries is addressed while providing an update and evidence-based knowledge on how researchers, university teachers, oral health professionals and dental students should understand the etiopathogenesis of the caries process and should diagnose, assess risk, take treatment decisions, manage and monitor coronal caries at individual and population levels. Renowned cariologists from across the world have contributed to this book, encompassing sixteen chapters, all peer reviewed ad hoc by international experts. The chapters were designed as evidence-based reviews on relevant aspects of the state-of-the-art on coronal caries. Individual chapters might express different views about subjects included in this monograph - considered an enrichment of the book rather than a contradiction in terms. Great emphasis was placed on effective and biologically friendly management of coronal caries in daily practice, which includes, under a unique umbrella, both non-operative and operative treatments. Attention was paid to the evaluation of the success of the treatment performed by means of clinical and patient-reported outcomes. The content of this book is of interest to readers in the field of dentistry.
Keywords: CARIES DENTALES; CARIES DENTALES -- TRATAMIENTO